Identification of Indicators, Components, and Dimensions of the Curriculum of Successful Startups in Iran - Keshtkari, Zhinous; Fathi Vajargah, Kourosh; Poushaneh, Kambiz; Assareh, Alireza (Management Strategies and Engineering Sciences, 2025)
The present study aimed to identify the indicators, components, and dimensions of the curriculum of successful startups in Iran. The research method, in terms of purpose, was fundamental-applied, and in terms of data type, it was qualitative. From a paradigmatic perspective, the study falls within interpretive paradigms. The research population included scientific documents as well as academic and organizational experts. A non-random purposive sampling method was used to select interviewees based on the inclusion criteria. Data were collected through semi-structured interviews. To assess validity, four criteria—credibility, dependability, transferability, and confirmability—were employed. The reliability of the research instrument was evaluated and confirmed using the inter-coder agreement method. In this study, hermeneutic (interpretive) phenomenology, with an emphasis on Van Manen’s approach, was utilized to explore the lived experiences of startup managers and experts regarding the phenomenon of startup curriculum. The curriculum of successful startups in Iran encompasses the dimensions of innovation and creativity, business management and strategy, product development, human resource management and team building, marketing, and sales. Additionally, to improve the curriculum, several recommendations were proposed, including aspects related to innovation culture, skills training and development, long-term strategy formulation, the use of project management tools, market research, continuous testing and improvement, talent acquisition and retention, professional development training, precise budgeting, legal consulting, digital marketing utilization, and data analysis. The findings of this study can contribute to a more precise understanding of the curriculum of successful startups in Iran and, by providing a comprehensive explanation, enhance startup curricula in Iran. These outcomes are of significant importance to research beneficiaries, including managers, policymakers, and startup investors, as they can lead to optimal decision-making and the improvement of managerial and supervisory strategies.